Junie B. Jones smells something fishy / 12. - Park, Barbara (Junie B. Jones, 1998)
Frustrated because the rules for her class's Pet Day will not let her take her dog to school, Junie B. Jones considers taking a raccoon, a worm, a dead fish, and other unusual replacements.